University Spin-off Formations: How decision making process has been made? - Ismail, Kamariah; Mason, Colin; Cooper, Sarah; Wan Omar, Wan Zaidi; Abdul Majid, Izaidin (Center for Promoting Ideas, 2010)
Commercialisation of intellectual property (IP), particularly patent becomes an important agenda in most universities. Patents that were licensed to established companies in return for royalties recognised as a traditional mode to commercialise university IPs. As government funding are getting harder to obtain, and demand from the stake holders to see universities play more important role in local economic development, universities are prompts to look at spin-off formations as an alternative route for technology commercialisation. This paper is trying to look into the process of decision making in commercialisation of university patents through spin-off formation. A single case of one university in Scotland is adopted in this study. Six patents from university portfolio’s patents were selected, which were licensed to spin-off companies. Companies that licensed know-how or IPs other than patents were excluded. The inventors of these 6 patents were interviewed in depth using semi-structured questionnaires, which were recorded and later transcribed. The data were then analysed using a case basis and cross-case analysis aided with Nvivo software. The study found that the decision making to seek patents protection was made by the inventors, and the Technology Transfer Office (TTO). On the other hand, the decision to commercialise the patents through the spinoffs creation were initiated by the inventors alone, not by the TTO. The study also revealed that the stage or performance of the technologies and the entrepreneurial characteristics of the inventors lead their patents were commercialised through spin-offs. Inventors industrial working experiences prior to their research positions in the University, were able to recognise the potential values of their technologies. This factor was found to be the most significant that drove them to form spin-offs. Their experiences meant they had better knowledge about potential market, market size as well as the standing of their technologies in the market place. Other important factors were the role and supports of Technology Transfer Office as well as the availability of funding. The result of this study could help policy makers in universities to consider: what are the characteristics of the inventions and the inventors, the availability of funding as well as the roles of technology transfer offices in their decision-making to spin-offs.